The Importance of Perceived Procedural Justice Among Defendants With a Non-Western Background Involved in Dutch Criminal Cases - Ansems, Lisa F. M.; van den Bos, Kees; Mak, Elaine (Frontiers in Psychology, 2021)
This study aims to put perceived procedural justice to a critical test in the context of Dutch criminal court hearings. To that end, we surveyed 198 criminal defendants to examine whether their perceptions of procedural fairness were significantly associated with trust in judges and intentions to protest against judicial rulings, among other variables. We also examine the possibility that sometimes unfair procedures may have nice aspects, because they offer opportunities to attribute negative outcomes to external causes. Previous studies conducted in different settings support this line of reasoning by showing that associations between perceived procedural justice and other variables are sometimes attenuated or even reversed, particularly when people feel strongly evaluated. The current study takes these insights to the novel context of Dutch criminal court hearings by focusing on defendants with a non-Western ethnic-cultural background. Some of these defendants may feel negatively evaluated by society, which can manifest as a high level of perceived discrimination. Thus, we examine whether the associations between perceived procedural justice and important other variables may be attenuated or reversed depending on respondents’ perceptions of everyday discrimination and their outcome judgments. Our results revealed significant associations between perceived procedural justice on the one hand and trust in judges and protest intentions on the other hand, which remained intact regardless of perceptions of everyday discrimination and outcome judgments. Hence, even in this real-life courtroom context, procedural justice was a relevant concern. Taken together, our findings support the importance of perceived procedural justice, even when it is put to a critical test.